The impact and cost-effectiveness of 9-valent human papillomavirus vaccine in adolescent females in Hong Kong - Tak Hong Cheung (BMC, 2021)
Abstract Introduction In Hong Kong (HK), a single-cohort vaccination program for 10–12-year-old girls with the 9-valent human papillomavirus (HPV) vaccine (9vHPV; types 6/11/16/18/31/33/45/52/58) has been launched. This study assessed the public health impact and cost-effectiveness of implementing routine 9vHPV vaccination (12-year-olds) with or without catch-up 9vHPV vaccination (13–18-year-olds) in HK. Methods The health impact and costs of implementing routine 9vHPV vaccination with or without catch-up vaccination over a 100-year time horizon were evaluated using a validated HPV-type transmission dynamic model adapted to the HK population; analyses were performed from a healthcare payer perspective. Routine vaccination (12-year-old girls) and catch-up vaccination (13–18 years) assumed vaccine coverage rates of 70% (base case) and 30%, respectively. The model also assumed herd immunity, lifelong vaccine protection, a discount rate of 3%, and a cost per dose of HK dollars (HKD) 858 [United States dollars (USD) 110] and HKD 1390 (USD 179) for the 2-valent HPV (2vHPV) and 9vHPV vaccines, respectively. HPV disease-related incidence and the incremental cost-effectiveness ratio (ICER) per quality-adjusted-life-year (QALY) were estimated. Cost-effectiveness was determined at a ceiling threshold of HK dollars (HKD) 382,046 (USD 49,142) or 1.0 times the gross domestic product per capita of HK. Results Compared with routine 9vHPV alone, routine plus catch-up 9vHPV is projected to reduce cervical cancer incidence by 3.4%. Routine plus catch-up 9vHPV will also reduce genital warts incident cases for males/females by 2.6%/5.4%. The incremental cost-effectiveness ratios were HKD 29,911 (USD 3847)/quality-adjusted life-year (QALY) for routine plus catch-up 9vHPV versus routine 9vHPV alone and HKD 25,524 (USD 3283)/QALY for routine 9vHPV alone versus screening only. Sensitivity analyses indicated that routine plus catch-up 9vHPV compared with routine 9vHPV alone remained cost-effective at coverage rates of 30% and 90%. Conclusions This analysis predicts that the current HK vaccination strategy can be considered cost-effective and will provide maximum health benefit. These results support addition of the routine 9vHPV vaccine with or without catch-up 9vHPV vaccination to the regional vaccination program in HK.